Pelatihan Pengembangan Asesmen Berbasis High Order Thinking Skills (HOTS) Bagi Guru MIPA SMP di Kotabumi Lampung Utara - Berti Yolida; Rini Rita T. Marpaung; Median Agus Priadi; Agung Putra Wijaya (Universitas Muhammadiyah Manado, 2023)
The development of this thinking ability through education, with education students can make the best use of the information they have. The observation results show that most of the teachers have not used HOTS-based assessments. This is very concerning because students are only fed by learning with the old pattern, namely students are only learning objects with the lecture method. The aim of the training is to increase teachers' understanding of assessment, increase teachers' understanding of the HOTS-based assessment concept and efforts to improve teachers' skills in developing in learning evaluation. Training methods Lectures and demonstrations. The success of the implementation of this training is determined based on pre-test and post-test data using a Likert scale. The results of increasing the pre-test and post-test scores in this community service activity show the criteria of